PROSES MORFOFONEMIK DALAM BAHASA JEPANG - Nasution, Sari Suti H. (Center of Language and Cultural Studies, 2017)
This study examines process of morphophonemics in Japanese language. This qualitative study used content analysis as the research design approaching the analysis in qualitative approach. Corpus of this study included words, phrases, sentences and discourse obtained from the two Japanese texts for children: minna no nihongo and Japenese films. Data were analyzed using interactive model: reduction, display, verification and conclusion drawing implementing morphophonemics theory of Koizumi. The study revealed that morphophonemics as a process order between morphology and phonology of a language occured in the Japanese texts for children stiries and the films: including fuka, sakujo, chikau, zero setsuji.